Uncovering overlooked bacterial infections in gene X-pert MTB/RIF negative sputum samples of adult patients with presumptive tuberculosis in Harar, Eastern Ethiopia - Negesso Gebre; Jemal Mohammed; Rudwan Yasin Abrahim; Mohammed Ahmed; Kedir Urgesa (PLoS ONE, 2026)
Background Lower respiratory tract infections are among the diseases that pose an existential threat to global public health. Clinical presentations of various bacterial lower respiratory infections and presumptive pulmonary tuberculosis are often overlap, hindering prompt patient care and correct diagnosis. In developing countries like Ethiopia, the management of presumptive tuberculosis cases that test negative for Gene Xpert is often empirical. Consequently, it is imperative to address potential overlooked bacterial infections in cases that are negative for tuberculosis. Objective This study aimed to determine the prevalence of pathogenic bacteria, antimicrobial susceptibility patterns, and associated factors of lower respiratory tract infection among Gene Xpert-negative presumptive tuberculosis adult patients at Hiwot Fana Comprehensive Specialized Hospital, eastern Ethiopia. Method A hospital-based cross-sectional study was conducted among 371 study participants from January 01 to April 30, 2024. Socio-demographic and health related data were collected using structured questionnaire. Gene Xpert MTB/RIF was used for initial tuberculosis screening, and sputum culture was used to isolate bacterial pathogens. Bacterial isolates were identified based on gram staining, colony characteristics, and biochemical reactions. Antimicrobial susceptibility test was done using Kirby-Bauer disc diffusion method. Methicillin resistance S. aureus was confirmed using cefoxitin (30 µg). Logistic regression analysis was used to assess the association between outcome and predictor variables. Results The overall prevalence of pathogenic bacterial lower respiratory tract infection was 34.0% (95% CI; 29.2, 38.8). Gram-negative bacteria accounted for 66.7%. S. aureus (19.0%) was the predominant isolate followed by K. pneumoniae (14.3%). The proportion of multi-drug resistant bacteria and methicillin-resistance S. aureus was 39.7% and 16.7% respectively. Primary education (AOR = 4.01; 95% CI = 1.62, 9.92), history of antibiotic usage (AOR = 1.87; 95% CI = 1.13, 3.08) and crowded living condition (AOR = 5.11; 95% CI = 3.03, 8.61) were factors associated with pathogenic bacterial lower respiratory tract infections. Conclusion This study revealed that patients with presumptive tuberculosis who tested negative on Gene Xpert- were predominantly infected with gram negative pathogenic bacteria. Therefore, it’s important to prioritize sputum culture and antibiotic susceptibility testing. This study underscore the need to avoid the misuse of antibiotics and crowded living conditions.